Sam battles the machine - Chabert, Jack; Ricks, Sam (New York, NY : Scholastic Inc., 2017)
Sam, Lucy, and Antonio have a new substitute teacher, who happens to be the great-great-grandson of Orson Eerie, the evil scientist whose spirit possesses and infects their elementary school--and the friends are afraid he may be trying to bring Orson back to life.
3.5
K-3
470L
Keywords: Elementary schools -- Juvenile fiction; Haunted schools -- Juvenile fiction; Substitute teachers -- Juvenile fiction; Best friends -- Juvenile fiction; Elementary schools -- Fiction; Schools -- Fiction; Haunted places -- Fiction; Substitute teachers -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Horror fiction